THE CLASSICAL POLITICAL ECONOMY: CRITICISM AND CONTROVERSY AROUND THE MID-NINETEENTH CENTURY - MORSELLI, Alessandro (Theoretical and Practical Research in Economic Fields; Vol 10 No 1 (2019): TPREF, Volume X, Issue 1(19), Summer 2019, 2019)
The present work highlights the insufficiency of classical methodology to explain economic phenomena. The classical formulation left the notion of value unspecified, so there is room for the marginalist current, which abandons the classic value-work theory of the and replaces it with a theory of value based on marginal utility. The scenario changes and the attention is no longer paid to the classical social aggregates, but to individuals and economic subjects, passing from objectivity to the subjectivity of individual choices. From the marginalist principles, which still have an important influence today, the neoclassical school is constituted, which sets itself the objective of highlighting the advantages of economic liberalism, already highlighted by classical authors, but through different instruments compared to those used in the past. In this way we will have the opportunity to observe how the study of economics becomes more scientific, general and universal.